The Relationship Between Body Mass Index and In-Hospital Mortality in Patients Following Coronary Artery Bypass Grafting Surgery - Elbaz-Greener, Gabby; Rozen, Guy; Carasso, Shemy; Kusniec, Fabio; Yarkoni, Merav; Marai, Ibrahim; Strauss, Bradley; Wijeysundera, Harindra C.; Smart, Frank W.; Erez, Eldad; Alcalai, Ronny; Planer, David; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between Body Mass Index (BMI) and clinical outcomes following coronary artery bypass grafting (CABG) remains controversial. Our objective was to investigate the real-world relationship between BMI and in-hospital clinical course and mortality, in patients who underwent CABG. Methods: A sampled cohort of patients who underwent CABG between October 2015 and December 2016 was identified in the National Inpatient Sample (NIS) database. Outcomes of interest included in-hospital mortality, peri-procedural complications and length of stay. Patients were divided into 6 BMI (kg/m2) subgroups; (1) under-weight ≤19, (2) normal-weight 20–25, (3) over-weight 26–30, (4) obese I 31–35, (5) obese II 36–39, and (6) extremely obese ≥40. Multivariable logistic regression model was used to identify predictors of in-hospital mortality. Linear regression model was used to identify predictors of length of stay (LOS). Results: An estimated total of 48,710 hospitalizations for CABG across the U.S. were analyzed. The crude data showed a U-shaped relationship between BMI and study population outcomes with higher mortality and longer LOS in patients with BMI ≤ 19 kg/m2 and in patients with BMI ≥40 kg/m2 compared to patients with BMI 20–39 kg/m2. In the multivariable regression model, BMI subgroups of ≤19 kg/m2 and ≥40 kg/m2 were found to be independent predictors of mortality. Conclusions: A complex, U-shaped relationship between BMI and mortality was documented, confirming the “obesity paradox” in the real-world setting, in patients hospitalized for CABG.